Café Lumière - Hou Hsiao Hsien; Lee Ping Bing; Hitoto, Yo; Asano, Tadanobu; Hagiwara, Masato (Drakes Avenue Pictures, 2005)
"Café Lumière" concentrates on the minutiae of everyday life, such as preparing and eating food, drinking coffee in cafés, and travelling around Tokyo by tram and train. Yoko is researching a book on the Taiwanese-born composer Jiang Wenye - whose work appears on the soundtrack - and she is trying to track down the musician's 1930 haunts. Hajime is happy to help in this research, whilst continuing to pursue his pet project of recording the sounds of the city's extensive rail network. [www.bbc.co.uk]
Keywords: DVD-Video